2018
DOI: 10.1080/16549716.2018.1461338
|View full text |Cite
|
Sign up to set email alerts
|

Does expanding fiscal space lead to improved funding of the health sector in developing countries?: lessons from Kenya, Lagos State (Nigeria) and South Africa

Abstract: Background: The global focus on promoting Universal Health Coverage has drawn attention to the need to increase public domestic funding for health care in low- and middle-income countries. Objectives: This article examines whether increased tax revenue in the three territories of Kenya, Lagos State (Nigeria) and South Africa was accompanied by improved resource allocation to their public health sectors, and explores the reasons underlying the observed trends. Methods: Three case studies were conducted by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Chronic underfunding of public health has negatively influenced the ability of existing health systems in African countries to respond to healthcare needs [1], p. 249. In South Africa, despite increases in public healthcare utilisation due to the high burden of disease and increased patient load over the period 1997-2010, the public health sector fell from second to fourth in the list of spending priorities [2]. Consequently, major health system challenges occurred in this sector including negative staff attitudes, long waiting times, unclean facilities, medicine stock-outs, insufficient infection control and compromised safety and security of both staff and patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic underfunding of public health has negatively influenced the ability of existing health systems in African countries to respond to healthcare needs [1], p. 249. In South Africa, despite increases in public healthcare utilisation due to the high burden of disease and increased patient load over the period 1997-2010, the public health sector fell from second to fourth in the list of spending priorities [2]. Consequently, major health system challenges occurred in this sector including negative staff attitudes, long waiting times, unclean facilities, medicine stock-outs, insufficient infection control and compromised safety and security of both staff and patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous qualitative research has examined Nigerian government stakeholders' perspectives on FP programming and policies [18][19][20] and government stakeholders' perspectives on the long-term sustainability and financing of various health programs, including health systems strengthening and maternal and child health services [19,21,22]. Yet there has been little research on government stakeholders' perspectives on the FP environment and how actors influence the sustainability of programming efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the question of whether the expansion of the social health insurance programme, which causes inevitable increase in fiscal resources in the forms of tax revenues, grants, or subsidies, actually result in better financing capabilities of the government, is unsettling. For example, a recent comparative study of three countries in Africa (Kenya, Nigeria and South Africa) has concluded that the improvement of tax revenue collections in these countries did not improve the fiscal space for health due to other competing developmental priorities …”
Section: Introductionmentioning
confidence: 99%